A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Première publication 1892 https://docsouth.unc.edu/church/cooper/cooper.html
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Nānīawig Māmawe Nīnawind. Debout et solidaires. Femmes autochtones disparues ou assassinées au Québec - Québec, Femmes autochtones au; Bergeron, Annie; Boileau, Alana; Lévesque, Carole (Femmes autotchtones au Québec, 2015)
Le présent document fait état des résultats d’une enquête exploratoire effectuée par Femmes Autochtones au Québec (FAQ) en ce qui a trait à la situation des femmes autochtones disparues ou assassinées au Québec. Cette enquête a bénéficié du soutien financier du ministère de la Justice du Québec et du Réseau de recherche et de connaissances relatives aux peuples autochtones (DIALOG). Elle visait principalement à consigner et à mettre en valeur la parole des Autochtones de différents horizons et provenances, de même que celles des membres des familles de femmes autochtones disparues ou assassinées, principales personnes concernées par la problématique.
Keywords: amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; justice sociale; pol4105; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La justice reproductive, ou l'application du prisme de la justice sociale à la santé et aux droits sexuels, reproductifs et maternels - Fédération du Québec pour le Planning des naissances (Fédération du Québec pour le planning des naissances, 2014)
La justice reproductive est à la fois un cadre d’analyse et de pratiques et un mouvement social qui a émergé aux États-Unis pendant les années 1990. Le terme a été consacré par des femmes africaines-américaines lors de la Conférence internationale sur la population et le développement qui a eu lieu au Caire en 1994. Il est le résultat de l’amalgame entre « justice sociale » et « droits reproductifs ». La justice reproductive situe l’accomplissement de la pleine autonomie sexuelle et reproductive des femmes et des filles au sein d’un projet plus large de justice sociale. Ce mouvement a émergé de l’initiative de femmes racisées et autochtones et continue d’être majoritairement porté par elles.
Keywords: amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; femmes* autochtones; femmes* racisées; inégalités; justice reproductive; justice sociale; maternité; privilèges; québec; racisme; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; états-unis

Les féministes blanches et l'Empire - Boggio Éwangé-Épée, Félix; Magliani-Belkacem, Stella (La Fabrique, 2012)
Depuis la loi dite « sur le voile à l’école » de réelles fractures sont apparues entre les différentes composantes du mouvement féministe pour aboutir à des clivages profonds en termes de mots d’ordre, d’actions et de mobilisations. Dans le même temps, l’offensive raciste s’est affermie, greffant à sa rhétorique la question des « droits des femmes ». Il est de plus en plus courant d’analyser ce virage en terme d’« instrumentalisation du féminisme à des fins racistes ». Ce livre entend précisément interroger et discuter cet énoncé. L’idée qu’un mouvement social, une politique d’émancipation, puissent être simplement utilisés, ou récupérés par l’ordre existant pour renforcer son discours rencontre bien des limites. Comment expliquer que la réaction ait pu soudainement se parer de vertus « féministes », elle qui a toujours été si hostile aux mouvements féministes, elle qui est si prompte à défendre le patriarcat ? Pour comprendre ce tournant, il faut envisager la chose non comme une simple « récupération » ou « instrumentalisation » mais plutôt comme une convergence d’intérêt, comme une affinité entre les objectifs, à court ou moyen terme, de larges franges du féminisme et du pouvoir raciste et impérialiste, à des moments historiques précis. C’est dans cette perspective que les auteur-e-s de ce court essai entreprennent une généalogie des stratégies féministes : non pas une histoire détaillée, mais plutôt un coup de projecteur sur des situations historiques où la question raciale et/ou coloniale s’est trouvée au cœur du discours des féministes. Les suffragettes et « la mission civilisatrice », le féminisme de la deuxième vague et, plus près de nous, l’épisode de la loi sur le voile à l’école ou encore celui de la solidarité internationale, constituent ces « moments » dont l’étude met à jour les logiques qui ont conduit certaines féministes à promouvoir leurs objectifs aux dépens des colonisé-e-s et descendant-e-s de colonisé-e-s. Le livre propose une discussion stratégique sur le féminisme et le racisme, un récit des occasions perdues et de certaines faiblesses héritées que les mouvements progressistes doivent comprendre et dépasser pour inventer des futurs émancipateurs.
Keywords: approches et analyses; cours; discipline; droits des femmes*; europe; fem1000; fem3100; france; histoire; histoire et politique; mouvements féministes; pratiques féministes; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Advocating from the margins: The reproductive justice movement and the politics of oppositional consciousness - Kirwood, Zachary (Wesleyan University, 2012)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; droits des femmes*; histoire et politique; intersectionnalité; justice reproductive; mémoires/thèses; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; états-unis; étude qualitative

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences